A Multicenter, Longitudinal Cohort Study of Cryptococcosis in Human Immunodeficiency Virus–negative People in the United States. (11th March 2019) - Marr, Kieren A; Sun, Yifei; Spec, Andrej; Lu, Na; Panackal, Anil; Bennett, John; Pappas, Peter; Ostrander, Darin; Datta, Kausik; Zhang, Sean X; Williamson, Peter R; ,
Abstract: Background: Cryptococcosis is increasingly recognized in people without human immunodeficiency virus (HIV). Methods: A multicenter, prospective cohort study was performed in 25 US centers. Consenting patients were prospectively followed for ≤2 years. Neurological morbidities were assessed with longitudinal event depiction and functional scores (Montreal Cognitive Assessment [MoCA]). Risks of death were analyzed using Cox regression. Results: One hundred forty-five subjects were enrolled. Most were male (95; 65.5%) and had immunosuppression (120; 82.8%), including solid organ transplant (SOT; 33.8%), autoimmunity (15.9%), and hematologic malignancies (11.7%). Disease involved the central nervous system (CNS) in 71 subjects (49%). Fever was uncommon, documented in 40 (27.8%) subjects, and absence was associated with diagnostic delay (mean: 48.2 vs 16.5 days; P = .007). Abnormal MoCA scores (<26) were predictive of CNS disease; low scores (<22) were associated with poor long-term cognition. Longitudinal event depiction demonstrated frequent complications in people with CNS disease; 25 subjects (35.2%) required >1 lumbar puncture and 8 (11.3%) required ventriculostomies. In multivariable models, older age (>60 years) was associated with higher risks of death (hazard ratio [HR], 2.14; 95% confidence interval [CI], 1.05–4.38; P = .036), and lower risks were noted with underlying hematologic malignancy (HR, 0.29; 95% CI, 0.09–0.98; P = .05) and prior SOT (HR, 0.153; 95% CI, 0.05–0.44; P = .001). Conclusions: Despite aggressive antifungal therapies, outcomes of CNS cryptococcosis in people without HIV are characterized by substantial long-term neurological sequelae. Studies are needed to understand mechanism(s) of cognitive decline and to enable better treatment algorithms. Abstract : A longitudinal cohort study of people with cryptococcosis occurring without an underlying diagnosis of human immunodeficiency virus demonstrates delayed diagnoses and persistent neurological sequelae despite antifungal therapy.